Differential expression of RNA exosome subunits in the amphibian Lithobates catesbeianus during reproductive and non-reproductive periods - Luz, J. S. [UNESP]; Caneguim, B. H.; Baggio, A. [UNESP]; Santoni, M. M. [UNESP]; Helbing, C. C.; Valentini, S. R. [UNESP]; Sasso-Cerri, E. [UNESP]; Oliveira, C. C. (Springer Nature, 2019)
Objective: The RNA exosome is an evolutionarily conserved 3′-5′ exoribonucleolytic protein complex involved in processing and degradation of different classes of nuclear and cytoplasmic RNAs, and, therefore, important for the posttranscriptional control of gene expression. Despite the extensive in vivo functional studies and the structural data on the RNA exosome, few studies have been performed on the localization and expression of exosome subunits during gametogenesis, process during which gene expression is largely controlled at the posttranscriptional level. Results: We report the identification of exosome subunits in Lithobates catesbeianus and analysis of the differential subcellular localization of RNA exosome core and catalytic subunits in testis cells. In addition, we show seasonal differences in the expression levels of four exosome subunits in different organs. In addition to being part of the RNA exosome complex, its subunits might participate independently of the complex in the control of gene expression during seasonal variation in bullfrog tissues. These results may be relevant for other eukaryotic species.
Keywords: Lithobates catesbeianus; Protein localization; RNA exosome; Tissue expression